What we know and don’t know about the antenatal care service utilization in Ethiopia: A scoping review of the literature - Amanuel Yoseph; Kibru Kifle; Yohannes Seifu Berego; Mehretu Belayneh; Alemu Tamiso; G. Mutwiri; Francisco Guillen-Grima (PLoS ONE, 2025)
Introduction In Ethiopia, there has been considerable recent investment and prioritization in the maternal health program. However, coverage rates have been low and stagnant for a long time, indicating the existence of systemic utilization barriers. Therefore, it is fundamental to synthesize the current body of knowledge to successfully address these problems and enhance program effectiveness to increase antenatal care (ANC) uptake. Methods We conducted a scoping review of the literature. Using various combinations of search strategies, we searched Pubmed/Medline, WHO Library, ScienceDirect, Cochrane Library, Google Scholar, and Google for this review. Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) were used to conduct the review. We included studies that used any study design, data collection, and analysis methods related to antenatal care utilization. Results A total of 76 studies, national surveys, and estimates were included in this review. The analysis revealed that ANC utilization coverage varied considerably by region, from 27% in Somali to 90.6% in the Oromia region, with significant disparities in socioeconomic status, access to healthcare, and vaccination knowledge. Ten priority research areas covering various aspects of the national ANC services were identified through a comprehensive review of the existing body of knowledge led by experts using the Delphi method. Conclusion The barriers to recommended ANC service utilization differ depending on the context, suggesting that evidence-based, locally customized interventions must be developed and implemented. This review also identified evidence gaps, focusing on health system-related utilization barriers at the lower level, and identified additional research priorities in Ethiopia’s ANC service. The first step in developing and executing targeted program approaches could be identifying coverage of ANC services utilization among those with disadvantages.